The microbiota in eosinophilic esophagitis: A systematic review. Issue 9 (12th July 2022) - Angerami Almeida, Kaylani; de Queiroz Andrade, Ediane; Burns, Grace; Hoedt, Emily C; Mattes, Joerg; Keely, Simon; Collison, Adam
Abstract: Eosinophilic esophagitis (EoE) is an atopic disease of the esophagus that has shown a significant increase in incidence and prevalence in the last 20 years. The etiology of EoE is unclear, and few studies explore the esophageal microbiota in EoE. The local microbiome has been implicated in the pathogenesis of several allergic and inflammatory diseases, such as asthma and eczema. In this study, we performed a systematic review to evaluate differences in the microbiota profile of patients with EoE compared with controls. MEDLINE, Embase, Cochrane Library, Scopus, and CINAHL (Cumulative Index to Nursing and Allied Health Literature) databases were searched to identify studies investigating the microbiota composition in EoE. Three reviewers screened the articles for eligibility and quality. Seven articles underwent full‐text review, and a narrative synthesis was undertaken. The microbiota of the mouth and esophagus are correlated. Patients with active EoE present increased esophageal microbial load and increased abundance in particular species, such as Haemophilus and Aggregatibacter. On the other hand, EoE patients present a decrease in Firmicutes. High microbial load and abundance of Haemophilus are observed in EoE patients, but little evidence exists to demonstrate their influence on inflammation and disease. Understanding microbial signatures in EoE might contribute to the development of novel therapeutic strategies.